Biogas production from co-digestion of Pennisetum pururem cv. Pakchong 1 grass and layer chicken manure using completely stirred tank - Wilawan W. (Elsevier Ltd, 2014)
In this research, the production of biogas from co-digestion of Pennisetum purpureum cv. Pakchong 1 grass and layer chicken manure using completely stirred tank was investigated. The experiment was defined to examine effect of the change in carbon to nitrogen (C/N) ratios and the organic loading rates (OLRs) on biogas production and system steady-state performance. Primary analyses suggested that an approximate content of grass and manure was 50 : 50% by weight to achieve C/N ratio of 20 and 70 : 30% by weight for C/N ratio of 30 respectively. The experimental reactor was set to operate at a fixed total solid content of 4% with two cases of C/N ratio at four different OLRs of 1.1, 1.4, 1.7 and 2.2 kg VS/ (m3.d). Each condition was operated for 1.5 time of reactor retention time. The result suggested that maximum steady-state methane yield of 0.27 ± 0.01 L CH4/kg VSadded can be achieved at C/N ratio of 20 with OLR of 1.1 kg VS/ (m3.d). Moreover, the results also suggested that methane yield decreased for an increase in OLR. Nonetheless, the work presented herein can provide an insight information for design and operation optimization according to economical investment analysis. © 2014 Published by Elsevier Ltd.